OPTIMIZING EMPLOYEE PERFORMANCE THROUGH EFFECTIVE WORK DISCIPLINE, WORK EXPERIENCE AND WORK ENVIRONMENTAL - Nugroho, Novianto Eko (Makro Jurnal Manajemen Dan Kewirausahaan, 2025)
One of the main challenges faced by electronic cigarette distributor companies is low employee performance, which refers to the effectiveness and efficiency of employees in carrying out their duties and responsibilities according to organizational standards. This study aims to analyze the influence of work discipline, work experience, and work environment on employee performance in one of the electronic cigarette distributor companies in the Surabaya area. In this context, employee performance reflects the contribution of employees in achieving company goals optimally and sustainably. This research uses a quantitative descriptive approach, with a population of all employees in the company. The research sample was determined through simple random sampling, with a total of 66 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the help of the SPSS version 28 program. The analysis shows that work discipline sig. value of 0.013, work experience sig. value of 0.008, and work environment sig. value of 0.005 have a positive and significant effect on employee performance. The F test with a sig. value of 0.002 confirms that the regression model that combines the three variables is feasible and able to explain variations in employee performance simultaneously. This finding underscores the strategic role of work environment in improving employee performance, so companies need to create a work environment that supports workforce effectiveness. In addition, attention to work experience is crucial in maintaining employee well-being, which contributes to improving overall performance. By understanding the interrelationship between these three variables, companies can design more appropriate strategies to improve employee performance, while ensuring operational stability and business competitiveness in a growing industry.